Versatility of the submental island flap in head and reconstruction - Katre, Mahendra I.; Keche, Prashant; Gaikwad, Arvind; Deshmukh, Sunil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Head neck cancer is major cause of morbidity and mortality worldwide. India has one of the highest incidences of oral cancer and accounts for about 30% of all new cases annually. Ablative surgery is main stay of treatment which is followed by reconstructive surgery. Microvascular surgery revolutionized onco-reconstruction which requires great expertise even in tertiary cancer centre and it is not possible many times due to long waiting list for it or patient condition. Here there is role locoregional pedicled flap which mitigate this problem to great extent to achieve acceptable functional and aesthetic outcome. One such flap worth to keep in surgeon armamentarium is submental island flap. Submental artery island flap (SIF) is an axial fasciocutaneous flap that includes skin, subcutaneous tissue, platysma, and fat and is pedicled on the submental artery and veins. Methods: This study conducted in our institute a tertiary level cancer hospital. This is retrospective study. Data extracted from department database between periods February 2015 to May 2017. It includes 12 patients diagnosed with different sub site oral cancer, operated in department of head neck oncology for oral cancer and reconstruction fallowing ablative surgery done by submental island flap by ablative surgeon. Results: Submental island ﬂaps are comparable in their outcome with radial forearm free ﬂap. They carry a good color match with facial tissue. It is thin and has a reliable vascular morphology. Conclusions: When combined with the reported experience of other surgeons, our preliminary experience shows that the SIF is an excellent alternative in the reconstruction of head and neck defects because of its reliability, versatility, and relative ease of application. Neck dissection can plan as an adjunctive procedure to the SIF with certain limitation.